ANALISIS TINGKAT LITERASI DIGITAL: STUDI SURVEI SISWA SEKOLAH DASAR TINGKAT ATAS - Bahasoan, Nizmah Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to assess the digital literacy level of upper-grade elementary school students using a quantitative approach with a descriptive survey design. The study subjects involved 60 fourth, fifth, and sixth-grade students at State Elementary School 74 Ambon. Data were collected through a digital literacy questionnaire and analyzed descriptively using average scores and percentages. The results showed that students' digital literacy was generally in the high category. The aspect of access and utilization of technology for learning received the highest score, while the aspect of safe and responsible technology use was in the medium category. Furthermore, the level of digital literacy tended to increase with increasing grade level. These findings indicate the need to strengthen digital literacy, particularly in the aspects of security and responsible technology use.